CHARACTERIZATION OF HIGH MOBILITY GROUP NONHISTONE PROTEINS FROM DIFFERENTIATED NEUROPHILIC GRANULOCYTES (Journal of Sciences, Islamic Republic of Iran)
The quantitative changes of the high mobility group (HMG) nonhistone chromosomal proteins in nondividing, differentiated peritoneal exudate neutrophils were identified by their solubility, electrophoretic mobility on both SDS and acetic acid gels, densitometric traces and elution profile on CM-sephadex. The results indicated that in neutrophils, HMGl undergoes a considerable reduction (80%) compared to thymus proteins, However, HMG2 and HMG17 remain constant. Also, HMG14 was not detectable in neutrophils implying the possible role of the HMG proteins in genome function